The change of butterfly fauna (Lepidoptera: Papilionoidea and Hesperioidea) of the central water-basin of the Pilica river - Śliwiński, Zygmunt (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2002)
Results of 43 years investigations of butterfly of the river-basin Pilica were presented, in total 102 species were found 5 of them: Helroplerus morpheus (Pall.), Chazara briseis (L.), Minois dryas (Scop.), Pararge achine (Scop.) and Lysandra dorylas (Den. et Schiff.) are extinct now. The next 6 are endangered. It is: Colias palaeno (L.), Ephydryas aurinia (R ott.), Pseudophilotes balon (Berg.), Maculinea arion (L.), Vacciniina optilete (Knoch.) and Lysandra bellargus (Rott.).